Different Responses Of Efflurage And Shaking Manipulation In Reducing Muscle Pain Intensity - Nur Safitri, Hesty Olivia; Roepajadi, Joesoef; Susanto, Indra Himawan; Bakti, Ananda Perwira (UNIVERSITAS NEGERI MAKASSAR, 2024)
Physical activity with eccentric movements has the potential to cause delayed pain after 24 hours. Efflurage and shaking manipulation are thought to be able to reduce delayed pain due to these activities. This study attempts to prove this hypothesis by conducting a study with a pretest and posttest experimental design. 15 people were selected using a purposive sampling method and then divided into 3 groups (X1: efflurage, X2: shaking, X3: control). Delayed pain was produced through squats, sumo squats, and lunges in 4 sets of 12 repetitions. Efflurage and shaking manipulations were performed for 10 minutes. Pain intensity was measured using a visual analogue scale. Pain intensity was measured 24, 48, and 72 hours after eccentric activity. In the first 24 hours, all groups experienced excruciating pain (VAS> 8). After intervention, the VAS value of X1 decreased by 38% in the first 24 hours, then decreased by 23.8% in the second 24 hours, and decreased by 38% in the third 24 hours. Meanwhile, the VAS X2 value decreased consecutively from 46.34% to 21.95% to 29.26% in the first to third 24 hours. The influence and difference test of X1 and X2 showed significant results (p <0.05) in the measurements of 24, 48, and 72 hours. The conclusion of the study showed that the response of shaking manipulation in reducing pain intensity occurred in the first 24 hours, while effluent manipulation successfully eliminated pain completely at 72 hours.